Planktonic or non‐planktonic food in young‐of‐the‐year European perch Perca fluviatilis in ponds. Issue 2 (12th June 2014) - Bláha, M.; Šetlíková, I.; Peterka, J.; Musil, J.; Policar, T.
<x xml:space="preserve">Abstract</x> Higher biomass especially of some aquatic macrophyte species offered a higher density of phytophilous zoobenthos, but did not increase the proportion of non‐planktonic to planktonic prey in young‐of‐the‐year perch Perca fluviatilis. Both abundance and biomass of non‐planktonic prey dominated over planktonic prey in the pond with lower biomass of aquatic macrophytes and lower food. Survival of P. fluviatilis was lower (20%) in the pond with lower food than in the other pond (34%), however, specific growth rate (1·3% day−1) and final Fulton's condition factor of P. fluviatilis were similar in both ponds.